Green Accounting Towards Sustainable Development with Financial Performance as a Mediating Variable: A Case Study in the Consumer Non-Cyclicals Sector - Anastasya Novianti Sanusi; Enny Susilowati Mardjono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The purpose of this research is to investigate the influence of green accounting, financial performance, and sustainable development. The study examines how green accounting impacts financial performance and sustainable development, the effect of financial performance on sustainable development, and the role of green accounting in sustainable development through financial performance. The research was conducted on companies in the consumer non-cyclicals sectors listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. A total of 16 companies were selected using purposive sampling techniques, resulting in 64 observations. Data analysis was carried out using path analysis with the assistance of SPSS software. The findings indicate that green accounting does not have a significant impact on financial performance, but it can influence sustainable development. Additionally, financial performance was not found to directly affect sustainable development. Moreover, the study revealed that green accounting does not influence sustainable development through financial performance as a mediating variable.